BEST Industry Sdn. Bhd. / Siti Hawa Mohd Ngagipar ... [et al.] - Mohd Ngagipar, Siti Hawa; Zawawi @ Ismail, Nur Azima; Mohamed, Maharani; Md Sangidi, Halimatulilmi; Abdullah, Norasmanizan; Azizan, Mohd Khairi (Faculty of Architecture, Planning and Surveying, 2005)
Our company, named as BEST Industry Sdn. Bhd. are decided to establish a Private Limited Company business where have been decided as manufacturing a Fat Zapper Powder. It was located at Lot 3, Jalan Pelabur 23/1, 40300 Shah Alam, Selangor Darul Ehsan. There are a few factors that make us to select this business. First, we have identified sort of problem faced by public. The most critical one are the increasing number of obesity people. Everyone enjoys a good fatty meal from McDonalds, KFC, or any other fast food restaurant from time to time. Or maybe just a bag of chips, a candy bar, or an ice cream cone. All of these are food items which people consume on a regular basis and are full of fat. For years, the public has worried about the intake of fat from items such as these and has almost obsessed over weight, figures, and fat. With all the hype about liquid diets, diet pills, diet programs, etc. who wouldn't jump at the idea of an all natural solution. Because of this awareness, we decide to produce Fat Zapper Powder which aims to reduce the obesity patients among adults between 35 to 50 years old who love to eat fatty meals. Besides that, the company also wants to increase Malaysian healthy. The company has its own objectives which its target is to produce at least 30000 units of products in one year. The company wants to produce quality product which is approved by the Ministry of Health. The company wants to organize Health Society especially for obesity patients cooperate with Ministry of Health. The company also has an aim to market the product within Malaysia.